Quantum Mechanical Analysis of High Resolution NMR-Spectra of Some Tri-Substituted Benzenes - Sharma, D.K.; Rai, H.C. (Asian Journal of Chemistry, 2010)
High Resolution NMR-Spectra (recorded at 90 MHz and 270 MHz) of some three spin aromatic systems (ABC type), viz., 2,4-dichlorophenol and 3,4-dimethylphenol have been analysed quantum mechanically with the help of second-order perturbation theory. In both cases, δij /Jij suggests the failure of first order rule. The analysis of complex spectra was carried out with the help of successive iterations and convergence of the Jij's and δij's. With these converged values, intersities of several spectral transitions were calculated and then used to draw the theoretical stick-spectrum to compare them with experimental ones.